(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The current study investigates the behaviour of headed bar lap splices in reinforced concrete beam tension zones. The effect of many variables affecting the behaviour of flexural members with lap splice in tension zone was examined. Using four point loading, seven simply supported concrete beams were tested until failure occurred. Beams used were having same dimensions (220 x 250x 1600 mm), concrete strength (25Mpa) and same longitudinal reinforcement (µ= 0.616%). It was discovered that the behaviour of an RCC beam can be achieved in a spliced beam with a 100 percent cut off ratio when the splice length is equal to 27 db without any transverse reinforcement, or when the lap is equal to 15.5 db with transverse reinforcement. The analytical data from the research further reveals that, by using transverse reinforcement for the spliced zone, the mode of failure changed from brittle to flexure. It was also discovered that using the lap splice length specified by ACI 318-14 for headed bars without using confinement in the lap splice zone resulted in brittle failure of beams and reduced ductility.